The Level of Flexibility, Muscle Strength and Balance in the Elderly at Banjar Bhineka Nusa Kangin, Badung, Bali - Ni Made Rininta Adi Putri; Ika Darmayanti Agustin; Govinda Vittala (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
The elderly will experience changes in the structure and function of the systems in their body. These changes can be in the form of physical and biological changes such as blood pressure, pulse, muscle strength, muscle flexibility, and others. This research was conducted to determine the level of flexibility, muscle strength and balance in the elderly. The method used in this study is a quantitative method. The sample used was elderly > 60 years as many as 10 people (60-64=6, 65-69=4) who were taken using the total sampling method. The instruments used are 5 components of the Senior Fitness Test. The results showed that there was a significant decrease in the dynamic balance component.